(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Though sex has a very long history which has existed long before now, it has never taken the dimension and proportion it has taken in recent times. Sex as an industry has expanded over the last decades which has facilitated the exploitation of women world over but mostly in developing countries. The exploitation and expansion of the prostitution industry has gained scholarly recognition through the presence of affordable internet facilities. This paper examines the extent to which the internet promotes global prostitution and the place of social work practice in curbing this menace. Variables considered were global bride trafficking as well as video sex conferencing. Conceptual classifications on the internet and global prostitutions were reviewed accordingly, while social network theory was employed. The paper was a quantitative study with a sample of 230 participants selected purposively for the study. The sampling technique was convenience sampling. Statistical tool for testing the studies hypotheses was Chi-square tool at 0.05 level of significance. Findings revealed a significant relationship between internet and global bride trafficking and video sex conferencing through social media sites. The study concluded that, it is a clear evidence that the internet through social media sites have significant impact on global prostitution. The community has made the world a global village where sex is traded across borders. It however recommended the abolition of all sites and social media sites that promotes live sex conferencing. There should be effort geared toward the abolition and destruction of all obscene sites and media platform that promote pornography.